USING A â€œSNAKE AND LADDERâ€ GAME IN TEACHING SPEAKING TO YOUNG LEARNERS - Sofyan, Rudy; Sinar, T. Silvana; Tarigan, Bahagia; Zein, T. Thyrhaya (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Speaking is the basic as well as the most important skill that needs to be acquired by English language learners. It is advisable that learning speaking English should begin as early as possible; however, to teach speaking skill to young learners is not an easy task since their age is the age of playing. Teaching speaking to young learners requires a teacher to find the technique best work with children, one of which is through games. One of the games that is corresponding to the age of young learners is a snake and ladder game. This paper aims at describing how a snake and ladder game is used in teaching speaking to young learners. Based on the discussion on applying a snake and ladder game, it is concluded that this game is the right game to apply in teaching speaking to young learners. People during early ages like playing and dislikes studying, especially in a formal education. By using this game, the children (learners) do not realize that they learn to speak English because they enjoy playing the game. In addition, this game supports the issue of student-centered learning because the students are the ones who actively practice speaking, while the teacher acts as the learning facilitator who provides assistance if needed.